Essential oils as an alternative to inhibit the growth of lung cancer A549 cell lines - Abdullah, Nazurah; Hazahari, Noor Yuslida; Ahmad Nor, Yusilawati; Amid, Azura; Samsudin, Nurhusna (AIJR Publisher, 2023)
Lung cancer is the leading cause of cancer-related deaths worldwide and ranked in the top 10 of newly reported cases. Due to the fact that cancer manifests with the most common symptoms, such as cough, it is always discovered late. Some essential oils are viable medicinal sources due to their extensive history of usage in traditional medicine. This study aims to explore the efficacy of five possible essential oils, namely Clary sage, Frankincense, Marjoram, Myrrh, and Thyme, as a halal alternative therapy for lung cancer against the lung cancer A549 cell line. The evaluation of the cytotoxicity for the essential oils was done by MTT-assay test. According to these studies, Frankincense essential oils showed the most potential in suppressing the growth of cancer cells among the essential oils examined. It had the highest inhibition of cell growth, with 93.9% cell proliferation, compared to the others.